Preparation method and application of nano-porous high-activity catalyst
By using bauxite leaching residue to prepare nanoporous highly active catalysts, the problems of low catalytic efficiency of existing catalysts and difficulty in resource utilization of bauxite leaching residues are solved, and efficient removal of organic matter in sodium aluminate solution and recycling of resources are achieved.
Patent Information
- Application Number
- CN202411915504.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing catalysts have low catalytic efficiency, serious residues and difficulty in recycling when catalyzing wet oxidation to remove organic matter in sodium aluminate solution. The harmless treatment and resource utilization of bauxite leaching residues have problems such as difficulty in decaling and low recovery of valuable elements.
The nanoporous highly active catalyst is prepared by ultrasonic dispersion, acidification, pH adjustment, heating and calcination, etc., which is used to catalyze the degradation reaction of organic matter in sodium aluminate solution.
The prepared nanoporous high-active catalyst has a high specific surface area and pore volume, which adapts to acid, alkali and neutral environments, significantly improves the catalytic efficiency, reduces catalyst residue, and realizes efficient removal of organic matter and resource utilization of bauxite leaching residue.
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a nanoporous high-activity catalyst, belonging to the technical field of organic catalysis. Background Art
[0002] The harm of organic matter to the Bayer process of alumina production and the resource utilization of bauxite leaching residue, a difficult-to-treat solid waste, are key technical problems that restrict the sustainable development of the alumina industry. The existing catalytic wet oxidation technology for removing organic matter from sodium aluminate solution has problems such as low catalyst efficiency, serious residue, and difficulty in recycling. Bauxite leaching residue, as a solid hazardous waste associated with the alumina industrial process, has problems such as difficulty in dealkalization, low recovery rate of valuable elements, and high technical requirements for its harmless treatment and resource utilization. Summary of the invention
[0003] In view of the problems of low catalytic efficiency, serious residue and difficult recovery of catalysts in the prior art for catalytic wet oxidation to remove organic matter in sodium aluminate solution, as well as the problems of difficulty in dealkalization and low recovery rate of valuable resources in the harmless treatment of bauxite leaching residue, the present invention proposes a preparation method and application of a nanoporous high-activity catalyst. Bauxite leaching residue, a solid hazardous waste that is difficult to be harmlessly treated, is used as a raw material to prepare a nanoporous high-activity catalyst with a large specific surface area and pore volume. The catalyst is used to catalyze the degradation reaction of organic matter in sodium aluminate solution, thereby realizing the efficient removal of organic matter in the Bayer process and the resource utilization of bauxite leaching residue, a solid waste that is difficult to be harmlessly treated.
[0004] A method for preparing a nanoporous high-activity catalyst, the specific steps are as follows:
[0005] (1) mixing the bauxite leaching residue and the dilute sulfuric acid solution uniformly and dispersing them ultrasonically at a temperature of 90 to 99° C., adding concentrated sulfuric acid to adjust the pH value of the system to 2 to 4, and performing ultrasonic acidification for 120 to 180 minutes to obtain a suspension; preferably, the ultrasonic power is 110 to 660 W and the frequency is 40 kHz;
[0006] (2) adjusting the pH value of the suspension to 8-10 with a NaOH solution, subjecting the suspension to ultrasonic treatment at a temperature of 90-99° C. for 80-140 min, separating the solid from the liquid, drying, grinding and sieving the solid to obtain an active intermediate; preferably, the ultrasonic power is 110-660 W and the frequency is 40 kHz;
[0007] (3) adding the active intermediate and lignocellulose to a copper acetate-ethanol solution and ultrasonically treating for 8 to 12 hours to obtain a slurry; preferably, the ultrasonic power is 110 to 660 W and the frequency is 40 kHz;
[0008] (4) The slurry is placed in an air atmosphere and calcined at a temperature of 400-1000° C. to obtain a nanoporous high-activity catalyst.
[0009] Preferably, the mass concentration of the dilute sulfuric acid solution in step (1) is 8-15%, and the solid-liquid ratio (g:mL) of the bauxite leaching residue to the dilute sulfuric acid solution is 1:1-6.
[0010] Preferably, the concentration of the NaOH solution in step (2) is 20 to 60 g / L.
[0011] Preferably, the concentration of copper acetate in the copper acetate-ethanol solution in step (3) is 5-15 g / L, the mass ratio of active intermediate to lignocellulose is 1-5:3-6, and the mass ratio of copper acetate to the total mass of active intermediate and lignocellulose is 1-3:7.
[0012] Application of the nanoporous high-activity catalyst prepared by the method in catalytic degradation of organic matter in sodium aluminate solution;
[0013] Preferably, the application comprises the following specific steps:
[0014] The nanoporous high-activity catalyst, bauxite, calcium oxide and Bayer process circulating mother liquor are uniformly mixed, added into a high-pressure reactor and sealed, heated to a temperature of 220-260° C., oxygen is introduced, and after the introduction of oxygen is stopped, the reaction is carried out for 60-100 minutes to oxidatively leach the bauxite and simultaneously catalytically oxidize and degrade organic matter in the sodium aluminate solution; solid-liquid separation is performed to obtain bauxite leaching residue and a circulating leachate with organic matter removed.
[0015] More preferably, the solid-to-liquid ratio of the nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor is g:g:g:mL of 1-6:10-20:2.1-2.6:100.
[0016] More preferably, the oxygen introduction rate is 0.6 to 1.5 g / min, and the oxygen introduction time is 2 to 10 min.
[0017] The beneficial effects of the present invention are:
[0018] (1) The present invention uses bauxite leaching residue, a solid hazardous waste that is difficult to be harmlessly treated, as a raw material to prepare a nanoporous high-activity catalyst having a three-dimensional mesoporous structure and adaptability to acid, alkaline and neutral environments, and can catalyze the degradation of organic matter in sodium aluminate solution;
[0019] (2) The nanoporous high-activity catalyst of the present invention has a nanoporous structure, which can significantly improve the stability of the catalyst under high temperature and high pressure conditions and extend the service life of the catalyst;
[0020] (3) The bauxite leaching residue of the present invention is a hazardous waste generated during the production of alumina. It is used as a matrix to prepare a catalyst and reused in the Bayer process, which significantly reduces the production cost of the catalyst, improves economic benefits, and realizes the recycling of resources, reducing environmental pollution;
[0021] (4) The nanoporous high-activity catalyst of the present invention uses a small amount of catalyst in the process of catalytic degradation of organic matter in sodium aluminate solution, and the catalytic oxidation degradation of organic matter is thorough with high catalytic efficiency. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0023] Example 1: A method for preparing a nanoporous high-activity catalyst, the specific steps are as follows:
[0024] (1) mixing the bauxite leaching residue and the dilute sulfuric acid solution uniformly and ultrasonically dispersing them at a temperature of 90° C. for 120 min, adding concentrated sulfuric acid to adjust the pH value of the system to 2 and ultrasonically acidifying for 120 min to obtain a suspension; the mass concentration of the dilute sulfuric acid solution is 8%, and the solid-liquid ratio of the bauxite leaching residue to the dilute sulfuric acid solution is g:mL 1:6; the ultrasonic power is 110 W and the frequency is 40 kHz;
[0025] (2) adjusting the pH value of the suspension to 8 with a NaOH solution having a mass concentration of 20 g / L, subjecting the suspension to ultrasonic treatment at a temperature of 90° C. for 80 min, separating the solid from the liquid, drying the solid, grinding it, and sieving it through a 300-mesh sieve to obtain an active intermediate; the ultrasonic power is 110 W and the frequency is 40 kHz;
[0026] (3) adding the active intermediate and lignocellulose to a copper acetate-ethanol solution and subjecting the solution to ultrasonic treatment for 8 h to obtain a slurry; the copper acetate concentration in the copper acetate-ethanol solution is 5 g / L, the mass ratio of the active intermediate to the lignocellulose is 1:3, and the mass ratio of copper acetate to the total mass of the active intermediate and the lignocellulose is 1:7; the ultrasonic power is 110 W and the frequency is 40 kHz;
[0027] (4) calcining the slurry in an air atmosphere at 400° C. for 60 min to obtain a nanoporous high-activity catalyst;
[0028] The nanoporous high-activity catalyst is used to catalyze the degradation of organic matter in the sodium aluminate solution, and the specific steps are as follows:
[0029] The nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor are uniformly mixed, added into a high-pressure reactor and sealed, heated to a temperature of 220° C., oxygen is introduced, and the introduction of oxygen is stopped and reacted for 60 minutes to oxidatively leach the bauxite and simultaneously catalytically oxidatively degrade organic matter in the sodium aluminate solution; solid-liquid separation is performed to obtain bauxite leaching residue and a circulating leachate from which organic matter is removed; the solid-liquid ratio of the nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor is 1:20:2.6:100 g:g:g:mL; the oxygen introduction rate is 0.6 g / min, and the oxygen introduction time is 2 min;
[0030] After testing, the total organic carbon removal rate in the solution was 93.69%, of which the removal rate of sodium humate was 96.85% and the removal rate of sodium oxalate was 86.61%.
[0031] Example 2: A method for preparing a nanoporous high-activity catalyst, the specific steps are as follows:
[0032] (1) mixing the bauxite leaching residue and the dilute sulfuric acid solution uniformly and ultrasonically dispersing them at a temperature of 95° C. for 180 min, adding concentrated sulfuric acid to adjust the pH value of the system to 3 and ultrasonically acidifying for 160 min to obtain a suspension; the mass concentration of the dilute sulfuric acid solution is 12%, and the solid-liquid ratio of the bauxite leaching residue to the dilute sulfuric acid solution is g:mL 1:4; the ultrasonic power is 550 W and the frequency is 40 kHz;
[0033] (2) adjusting the pH value of the suspension to 9 with a NaOH solution having a mass concentration of 40 g / L, subjecting the suspension to ultrasonic treatment at a temperature of 95° C. for 120 min, separating the solid from the liquid, drying the solid, grinding it, and sieving it through a 300-mesh sieve to obtain an active intermediate; the ultrasonic power is 550 W and the frequency is 40 kHz;
[0034] (3) adding the active intermediate and lignocellulose to a copper acetate-ethanol solution, and ultrasonically treating for 12 hours to obtain a slurry; the copper acetate concentration in the copper acetate-ethanol solution is 10 g / L, the mass ratio of the active intermediate to the lignocellulose is 1:4, and the mass ratio of copper acetate to the total mass of the active intermediate and the lignocellulose is 2:7; the ultrasonic power is 550 W, and the frequency is 40 kHz;
[0035] (4) calcining the slurry in an air atmosphere at 800° C. for 90 min to obtain a nanoporous high-activity catalyst;
[0036] The nanoporous high-activity catalyst is used to catalyze the degradation of organic matter in the sodium aluminate solution, and the specific steps are as follows:
[0037] The nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor are uniformly mixed, added into a high-pressure reactor and sealed, heated to a temperature of 240° C., oxygen is introduced, and the introduction of oxygen is stopped and reacted for 80 minutes to oxidatively leach the bauxite and simultaneously catalytically oxidize and degrade organic matter in the sodium aluminate solution; solid-liquid separation is performed to obtain bauxite leaching residue and a circulating leachate from which organic matter is removed; the solid-liquid ratio of the nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor is 3:15:2.4:100 g:g:g:mL; the oxygen introduction rate is 1.2 g / min, and the oxygen introduction time is 10 min;
[0038] After testing, the total organic carbon removal rate in the solution was 99.98%, and sodium humate and sodium oxalate were completely removed.
[0039] Example 3: A method for preparing a nanoporous high-activity catalyst, the specific steps are as follows:
[0040] (1) mixing the bauxite leaching residue and the dilute sulfuric acid solution uniformly and ultrasonically dispersing them at a temperature of 99° C. for 180 min, adding concentrated sulfuric acid to adjust the pH value of the system to 4 and ultrasonically acidifying for 180 min to obtain a suspension; the mass concentration of the dilute sulfuric acid solution is 15%, and the solid-liquid ratio of the bauxite leaching residue to the dilute sulfuric acid solution is g:mL 1:6; the ultrasonic power is 660 W and the frequency is 40 kHz;
[0041] (2) adjusting the pH value of the suspension to 10 with a NaOH solution having a mass concentration of 60 g / L, subjecting the suspension to ultrasonic treatment at a temperature of 99° C. for 140 min, separating the solid from the liquid, drying the solid, grinding it, and sieving it through a 300-mesh sieve to obtain an active intermediate; the ultrasonic power is 660 W and the frequency is 40 kHz;
[0042] (3) adding the active intermediate and lignocellulose to a copper acetate-ethanol solution, and ultrasonically treating for 12 hours to obtain a slurry; the copper acetate concentration in the copper acetate-ethanol solution is 15 g / L, the mass ratio of the active intermediate to the lignocellulose is 5:6, and the mass ratio of copper acetate to the total mass of the active intermediate and the lignocellulose is 3:7; the ultrasonic power is 660 W, and the frequency is 40 kHz;
[0043] (4) calcining the slurry in an air atmosphere at 1000° C. for 120 min to obtain a nanoporous high-activity catalyst;
[0044] The nanoporous high-activity catalyst is used to catalyze the degradation of organic matter in the sodium aluminate solution, and the specific steps are as follows:
[0045] The nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor are uniformly mixed, added into a high-pressure reactor and sealed, heated to a temperature of 260° C., oxygen is introduced, and the introduction of oxygen is stopped and reacted for 100 minutes to oxidatively leach the bauxite and simultaneously catalytically oxidatively degrade organic matter in the sodium aluminate solution; solid-liquid separation is performed to obtain bauxite leaching residue and a circulating leachate from which organic matter is removed; the solid-liquid ratio of the nanoporous high-activity catalyst, bauxite, calcium oxide, and Bayer process circulating mother liquor is 6:20:2.6:100 g:g:g:mL; the oxygen introduction rate is 1.5 g / min, and the oxygen introduction time is 10 minutes;
[0046] After testing, the total organic carbon removal rate in the solution was 96.17%, of which the removal rate of sodium humate was 98.32% and the removal rate of sodium oxalate was 89.45%.
[0047] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a nanoporous high-activity catalyst, characterized in that: The specific steps are as follows: (1) mixing the bauxite leaching residue and the dilute sulfuric acid solution uniformly and dispersing them ultrasonically at a temperature of 90 to 99° C., adding concentrated sulfuric acid to adjust the pH value of the system to 2 to 4, and performing ultrasonic acidification for 120 to 180 minutes to obtain a suspension; (2) adjusting the pH value of the suspension to 8-10 with a NaOH solution, ultrasonically treating the suspension at a temperature of 90-99° C. for 80-140 min, separating the solid from the liquid, and drying, grinding, and sieving the solid to obtain an active intermediate; (3) adding the active intermediate and lignocellulose to a copper acetate-ethanol solution and ultrasonically treating for 8 to 12 hours to obtain a slurry; (4) The slurry is placed in an air atmosphere and calcined at a temperature of 400-1000° C. to obtain a nanoporous high-activity catalyst.
2. The method for preparing the nanoporous high-activity catalyst according to claim 1, characterized in that: The mass concentration of the dilute sulfuric acid solution in step (1) is 8-15%, and the solid-liquid ratio (g:mL) of the bauxite leaching residue to the dilute sulfuric acid solution is 1:1-6.
3. The method for preparing the nanoporous high-activity catalyst according to claim 1, characterized in that: The concentration of the NaOH solution in step (2) is 20-60 g / L.
4. The method for preparing the nanoporous high-activity catalyst according to claim 1, characterized in that: In step (3), the concentration of copper acetate in the copper acetate-ethanol solution is 5-15 g / L, the mass ratio of the active intermediate to the lignocellulose is 1-5:3-6, and the mass ratio of copper acetate to the total mass of the active intermediate and the lignocellulose is 1-3:
7.
5. Use of the nanoporous high-activity catalyst prepared by the method according to any one of claims 1 to 4 in catalytic degradation of organic matter in sodium aluminate solution.
6. The use according to claim 5, characterized in that: The specific steps include: The nanoporous high-activity catalyst, bauxite, calcium oxide and Bayer process circulating mother liquor are uniformly mixed, added into a high-pressure reactor and sealed, heated to a temperature of 220-260° C., oxygen is introduced, and after the introduction of oxygen is stopped, the reaction is carried out for 60-100 minutes to oxidatively leach the bauxite and simultaneously catalytically oxidize and degrade organic matter in the sodium aluminate solution; solid-liquid separation is performed to obtain bauxite leaching residue and a circulating leachate with organic matter removed.
7. The use according to claim 6, characterized in that: The solid-liquid ratio of the nanoporous high-activity catalyst, bauxite, calcium oxide and Bayer process circulating mother liquor is 1-6:10-20:2.1-2.6:
100.
8. The use according to claim 6, characterized in that: The oxygen introduction rate is 0.6-1.5 g / min, and the oxygen introduction time is 2-10 min.
Citation Information
Patent Citations
Method for removing organic matters in alumina mother liquor by oxidation process
CN110203954A
Method for removing organic matters in sodium aluminate solution through ultrasonic-heterogeneous catalytic ozonation
CN114534662A